“Women Are in the Village and Men Are Always in the Bush" - Robert Jarvenpa (Semiotic Review)
In subarctic Canada, Chipewyan (Dene) men’s meals have become a significant forum for talking about vexing shifts in relationships between men and women. While not necessarily resolving these issues, men’s bush meals emerge as a powerful clearinghouse of information, an expression of fellowship and community, an ongoing assessment of gender relations and, perhaps, compensation for what has been lost in recent transformations in men’s and women’s lives. Food, therefore, and the varied forms of discourse surrounding it, are inextricably part of and reflective of the social transformations impacting Chipewyan society. How these dynamics play out in the semiotics of actual meal-time conversation are explored in several case examples of men’s meal gatherings. In these settings, conversations about, around, through and as food embrace an ensemble of iconic, indexical and symbolic properties which underscore the dilemma of “missing women.” Thus, even as Chipewyan women have withdrawn from bush landscapes in recent history, men’s pervasive meal-time conversations about their wives and female relatives are a way of symbolically inserting them back into these spaces.